Association between human immunodeficiency virus serostatus and the prevalence of atrial fibrillation. Issue 29 (23rd July 2021) - Osuji, Ngozi; Haberlen, Sabina A.; Ashikaga, Hiroshi; Brown, Todd T.; Feinstein, Matthew J.; Witt, Mallory D.; Magnani, Jared W.; Soliman, Elsayed Z.; Wu, Katherine C.; Post, Wendy S.
Abstract : Abstract: Atrial fibrillation (AF) leads to increased risk for stroke. Human immunodeficiency virus (HIV) is associated with cardiovascular disease (CVD), although it is unclear if HIV is associated with AF. The purpose of this study was to evaluate the association between HIV serostatus and the prevalence of AF in the Multicenter AIDS Cohort Study. A cross sectional study was conducted among 1674 HIV-infected (HIV+) and uninfected (HIV–) men who completed resting 12-lead electrocardiograms, and/or ambulatory electrocardiogram monitoring. Multivariable logistic regression was used to evaluate the association between AF, defined as the presence of either AF or atrial flutter, and HIV+ serostatus. Associations were adjusted for demographic variables, and then also for CVD risk factors. HIV+ men were younger than HIV– men (median 55.5 vs 61.7 years, P  < .001) and were more frequently African-American (30.5% vs 17.8%, P  < .001). Most HIV+ men (81%) had undetectable viral load. The age and race adjusted prevalence of AF was 3.0% in HIV+ and 3.3% in HIV– men. There was only 1 case of AF among African-American men. There were no associations between AF and HIV serostatus after adjusting for demographic factors (odds ratio 0.76; 95% CI 0.37 to –1.58; P  = .47) or after further adjustment for CVD risk factors (odds ratio 0.84; 95% CI 0.39 to –1.81; P  = .66). We found no association between HIV and AF in this cohort in which viral replication among the HIV+ men is generally suppressed. The overall prevalence of AF was low and was rare in African-American men.